(untitled) (Biuletyn Kryminologiczny, 2023)
Przedmiotem artykułu jest po pierwsze próba odpowiedzi na pytanie: „Czy więźniowie mają prawo do rehabilitacji?” – prawo, za którym stoi roszczenie o konkretne usługi w postaci programów poprawczych lub tradycyjnych metod, jak praca i edukacja. Po drugie, próba porównania pojęć „resocjalizacja” i „rehabilitacja”, celem wyjaśnienia podobieństw i różnic. Po trzecie, artykuł wyjaśnia również, że odpowiedzi na to pytanie szukali studenci kierunku kryminologia, bazując na pięciu naukowych tekstach, a mianowicie: The Supreme Court and the Rehabilitative Ideal Chada Flansersa, Toward a Theory of Prisoners’ Rights Richarda L. Lippke, Rehabilitation as a Positive Obligation Sonji Meijer, Why dignity matters: Dignity and the right (or not) to rehabilitation from international and national perspectives Amandy Ploch, Do Criminal Offenders Have a Constitutional Right to Rehabilitation? Edgardo Rotmana oraz Inmate’s Right to Rehabilitation during Incarceration: A Critical Analysis of the United States Correctional System Sheldona Seigafo. Formułując swoją odpowiedź, studenci zidentyfikowali wspólny mianownik tego prawa – bo za takowe uznali prawo do rehabilitacji – jak godność osobista, której poszanowanie rodzi obowiązek państwa stworzenia oferty poprawczej dla więźniów celem odzyskania przez nich wolności i życia zgodnego z prawem. Po czwarte, artykuł przedstawia krótką analizę każdego z tekstów. The subject of this article is an attempt to answer the question, „Do prisoners have a right to rehabilitation?” – a right behind which is a claim for specific services in the form of correctional programs or traditional methods, such as work and education. Second, it attempts to compare the terms rehabilitation and rehabilitation to clarify the similarities and differences. Thirdly, the article also explains that the answer to this question was sought by criminology students based on five scientific texts, namely: The Supreme Court and the Rehabilitative Ideal, Chad Flansers, Toward a Theory of Prisoners’ Rights, Richard L. Lippke, Rehabilitation as a Positive Obligation, Sonja Meijer, Why dignity matters: Dignity and the right (or not) to rehabilitation from international and national perspectives, Amanda Ploch, Do Criminal Offenders Have a Constitutional Right to Rehabilitation?, Edgardo Rotman and Inmate’s Right to Rehabilitation during Incarceration: A Critical Analysis of the United States Correctional System, Sheldon Seigafo. In formulating their response, the students identified the common core of this right – for they considered the right to rehabilitation as such – as personal dignity, respect of which gives rise to the state’s obligation to create a correctional offer for prisoners in order to regain their freedom and live a lawful life. Fourth, the article provides a brief analysis of each text.